Energy Transition in Algeria: The Role of Natural Gas, Solar Energy, and Hydrogen in Supporting the Green Economy by 2030 - Ismail Seddiki; Abdellah Aidjouli; Youcef Houcine (Journal of Excellence for Economics and Management Research, 2026)
This study aims to analyze Algeria's vast potential in promoting the green economy by leveraging renewable energies, with a focus on major projects, economic opportunities, and the challenges associated with this transition. The major projects include the development of gas in the Berkine Basin, boosting gas production in the Hassi R'Mel field, the electrical interconnection between Algeria and Italy, the Southern Hydrogen Corridor, as well as solar power projects with capacities of 1000 and 2000 megawatts.These projects offer significant opportunities to enhance sustainable economic growth and reduce dependence on fossil fuels. However, Algeria faces challenges related to the need for regulatory framework development, securing large-scale investments, and enhancing technical skills. International cooperation and the implementation of incentive policies are crucial factors for turning these challenges into opportunities that support a sustainable green economy.